ANALISIS PENERAPAN PERHITUNGAN PPH 21 ORANG PRIBADI SEBELUM DAN SESUDAH PENERAPAN PP 58 DAN PMK 168 TAHUN 2023 PADA CV MUDA RIA - Astuti, Indriani Indah; Satriawan, Indra; Mayasari, Riana (Jurnal Riset Terapan Akuntansi, 2025)
The latest tax regulations adaptation in Indonesia, namely Government Regulation Number 58 of 2023 and Regulation of the Minister of Finance Number 168 of 2023 still have challenges. One of the companies that has not implemented this latest regulation is CV Muda Ria. A case study was conducted on CV Muda Ria to test the implementation of Government Regulation Number 58 of 2023 and Regulation of the Minister of Finance Number 168 of 2023. The research methodology used is descriptive qualitative, with data collection through of company documents, tax regulations, as well as interviews with CV Muda Ria management. Mathematical data analysis using formulas and calculations in accordance with Regulation of the Minister of Finance Number 168 of 2023 using Microsoft Excel. The results of the research shows that there is no difference in a case study of employee A of CV Muda Ria, before and after adaptations of Government Regulation Number 58 of 2023 and Regulation of the Minister of Finance Number 168 of 2023, payable income tax is NIHIL. Even though payable tax income is NIHIL, CV Muda Ria still has an obligation to calculate and report income tax in accordance with the latest regulations. Therefore, CV Muda Ria is highly recommended to adopt this new regulation for accurate calculation of Income Tax. Keywords: Calculation of Income Tax Article 21, Government Regulation 58 of 2023, Minister of Finance Regulation 168 of 2023